Comparison of four methods for morphometric evaluation of wounds (Research, Society and Development, 2022)
Measurement of wounds to document the healing process have an important role in the management of wounds. Digital cameras in smartphones are available and easy to use and taking pictures of wounds has becoming a routine. Analyzing digital pictures with appropriate software provides a rapid, clean and easy-to-use tool for measuring of wound area. A set of 160 digital pictures of wounds in rats was the basis of this study. Digital photographs were made by placing a rule next to the wound in parallel with the healthy skin and visualized with Image Tool, ImageJ, and AutoCaD® softwares. Measurement of wound area was carried out and was performed paired Student’s t-test and Principal Component Analysis (PCA) to compare manual rule-based technique and all softwares measurement of wounds. In conclusion, the manual rule-based technique overestimated wound size and Image Tools software provided a better, faster, and accurate measurement of the wound area. This software could routinely be used to document wound healing process.